FLO1, FLO5 and FLO11 Flocculation Gene Expression Impacts Saccharomyces cerevisiae Attachment to Penicillium chrysogenum in a Co-immobilization Technique - Moreno-García, Jaime; Martín-García, Francisco José; Ogawa, Minami; García-Martínez, Teresa; Moreno, Juan; Mauricio, Juan C.; Bisson, Linda F. (Frontiers in Microbiology, 2018)
A reoccurring flaw of most yeast immobilization systems that limits the potential of the technique is leakage of the cells from the matrix. Leakage may be due to weakly adherent cells, deterioration of the matrix, or to new growth and loss of non-adherent daughter cells. Yeast biocapsules are a spontaneous, cost effective system of immobilization whereby Saccharomyces cerevisiae cells are attached to the hyphae of Penicillium chrysogenum, creating hollow spheres that allow recovery and reutilization. This attachment is based on naturally occurring adherent properties of the yeast cell surface. We hypothesized that proteins associated with flocculation might play a role in adherence to fungal hyphae. To test this hypothesis, yeast strains with overexpressed and deleted flocculation genes (FLO1, FLO5 and FLO11) were evaluated for biocapsule formation to observe the impact of gene expression on biocapsule diameter, number, volume, dry mass, and percent immobilized vs non-immobilized cells. Overexpression of all three genes enhanced immobilization and resulted in larger diameter biocapsules. In particular, overexpression of FLO11 resulted in a five-fold increase of absorbed cells versus the wild type isogenic strain. In addition, deletion of FLO1 and FLO11 significantly decreased the number of immobilized yeast cells compared to the wild type BY4742. These results confirm the role of natural adherent properties of yeast cells in attachment to fungal hyphae and offer the potential to create strongly adherent cells that will produce adherent progeny thereby reducing the potential for cell leakage from the matrix.